Beliefs about social norms and racial inequalities predict variation in the early development of racial bias. Issue 2 (7th September 2021) - Rizzo, Michael T.; Green, Emily R.; Dunham, Yarrow; Bruneau, Emile; Rhodes, Marjorie
Abstract: Racism remains a pervasive force around the world with widespread and well documented harmful consequences for members of marginalized racial groups. The psychological biases that maintain structural and interpersonal racism begin to emerge in early childhood, but with considerable individual variation—some children develop more racial bias than others. The present study ( N  = 116; 4‐year‐old children) provides novel insights into the developmental mechanisms underlying the emergence of racial bias by longitudinally documenting how two psychological processes—normative beliefs about interracial friendships and explanatory beliefs about racial inequalities—developmentally predict the emergence of pro‐White/anti‐Black racial bias during early childhood. In a 6‐month, three‐wave, longitudinal study, we found that 4‐year‐old children's beliefs that their parents and peers do not value interracial friendships predicted increased racial bias in and across time and that children's endorsement of essentialist over extrinsic explanations for racial inequalities predicted the developmental trajectory of racial bias over time. These findings suggest that children's foundational beliefs about the social world developmentally predict the emergence of racial bias in early childhood and speak to the importance of early and persistent intervention efforts targeting children's normative beliefs about interracial friendships and explanatory beliefs about racial inequalities.